Hatching of parasitic nematode eggs: a crucial step determining infection. Issue 2 (February 2022) - Mkandawire, Tapoka T.; Grencis, Richard K.; Berriman, Matthew; Duque-Correa, María A.
Abstract : Although hatching from eggs is fundamental for nematode biology it remains poorly understood. For animal-parasitic nematodes in particular, advancement has been slow since the 1980s. Understanding such a crucial life-cycle process would greatly improve the tractability of parasitic nematodes as experimental systems, advance fundamental knowledge, and enable translational research. Here, we review the role of eggs in the nematode life cycle and the current knowledge on the hatching cascade, including the different inducing and contributing factors, and highlight specific areas of the field that remain unknown. We examine how these knowledge gaps could be addressed and discuss their potential impact and application in nematode parasite research, treatment, and control. Highlights: Egg hatching is induced by a wide variety of host, environmental, and physicochemical cues. Each parasitic nematode responds to specific hatching-inducing factors, reflecting the particularities of their interactions with their host. While well described for some species, for the majority of them knowledge on the triggers and processes behind hatching remains elusive. The egg stage is often the only life-cycle stage that can be readily sampled from patients and the environment. Understanding hatching will allow us to efficiently hatch eggs, supporting existing life-cycle models and the development of new in vivo and in vitro models of infection. Novel research technologies, including high-throughput sequencing, bacterial metagenomics, and mass spectrometry, can lead to discoveries in nematode-hatching biology with translational implications for human and agricultural parasite control.